Pengaruh Influencer, Promosi Dan Harga Terhadap Keputusan Pembelian Produk Skincare Avoskin (Studi Pada Mahasiswa FEB UNISMA Angkatan 2017-2019) - Ifa Kurnia Sari; Nur Hidayati; Andi Normala (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the influence of influencers, promotions and prices on purchasing decisions for Avoskin skincare products. This research is a quantitative research. The sample of this study was 96 respondents from the 2017-2019 FEB students. Data were analyzed using multiple linear regression analysis. Based on the results of data analysis, the results of the t-test indicate that: (1) Influencers have a positive effect on purchasing decisions for Avoskin skincare products for 2017-2019 FEB UNISMA students. (2) Promotion has a negative effect on purchasing decisions for Avoskin skincare products for 2017-2019 FEB UNISMA students. (3) Price has a positive effect on purchasing decisions for Avoskin skincare products for 2017-2019 FEB UNISMA students. Keywords: Influencer, Promotion, Price, Purchase Decision